Current situation of central nervous system tumour survivors in a spanish hospital - Ivonne Marcela Rincón-Mantilla; Blanca Herrero; Elena Herranz Valero; Fernando Robles-Bermejo; Alba Herrera-Olivares; Felisa Vázquez-Gómez; Álvaro Lassaletta (Anales de Pediatría (English Edition))
Introduction: Despite the increasing number of central nervous system (CNS) tumour survivors, long-term (LT) sequelae remain a substantial burden on their health through various life stages. The aim of our study was to evaluate late morbidity, health-related quality of life (HRQoL), self-esteem, functional status, adaptive behaviour, physical activity and social outcomes such as education, employment, relationship status and possession of a driver’s license, in addition to the role of LT effects of radiotherapy (RTx) on these outcomes. Methods: The study included 111 CNS tumour survivors with a minimum of 10 years of follow-up. The assessment of patients included a comprehensive clinical evaluation and psychological questionnaires: SF-36 for HRQoL and Rosenberg self-esteem scale. Functional status was assessed with the Lansky/Karnosky scales and adaptive behaviour with the Vineland-II scale. Patients also completed one questionnaire that assessed physical activity and another that assessed other social variables. Results: The mean current age of CNS tumour survivors was 20 years (range, 12–34). The median time since diagnosis was 13 years (range, 10–26). The median age at diagnosis was 6 years (range, 1–18). The most prevalent LT sequelae were neurologic (55%), followed by neuropsychiatric (53.1%) and endocrine (49.5%) sequelae. Survivors treated with RTx (n = 52) had poorer outcomes in terms of adaptive behaviour, educational attainment and relationship status compared to those who did not receive RTx, but we did not find differences in quality of life or self-esteem scores between these groups. Conclusion: We found a high prevalence of long-term sequelae in CNS tumour survivors, especially in those who received RTx. In these patients, LT sequelae have a significant impact on functional status and social outcomes, but not on quality of life or self-esteem. Resumen: Introducción: A pesar de la creciente población de supervivientes de tumores del sistema nervioso central en la infancia (TSNC), los efectos a largo plazo (ELP) siguen siendo una carga sustancial en las diferentes etapas de su vida. Este estudio buscó evaluar la morbilidad tardía y la calidad de vida relacionada con la salud (CVRS), Así como la autoestima, el estado funcional, el comportamiento adaptativo, la actividad física y otras variables sociales como la educación, el empleo, la relación de pareja y posesión de permiso de conducir, además del impacto que podría tener el tratamiento con radioterapia (RT) en todos estos aspectos. Métodos: Se incluyeron 111 Supervivientes de TSNC, con al menos 10 años de seguimiento. Se realizó una evaluación clínica y encuestas psicológicas: SF-36 para CVRS y Rosenberg para autoestima. Se estimó estado funcional con las escalas de Lansky/Karnosky y el comportamiento adaptativo con el Vineland-II, respondieron además una encuesta de actividad física y otra para las variables sociales. Resultados: Los Supervivientes de TSNC, tuvieron una mediana de edad actual de 20 años (12–34), tiempo de seguimiento de 13 años (10–26) y edad al diagnóstico de 6 años (1–18). Los ELP más prevalentes fueron los neurológicos (55%), seguidos de los neuropsicológicos (53,1%) y endocrinológicos (49,5%). Los Supervivientes de TSNC tratados con radioterapia tuvieron peores resultados en la Escala de Comportamiento Adaptativo, nivel educativo y relación de pareja, pero no se encontraron diferencias en las puntuaciones de calidad de vida, ni en autoestima. Conclusión: Los Supervivientes de TSNC presentan una alta prevalencia de efectos a largo plazo, especialmente aquellos que recibieron radioterapia. Estos ELP tienen un impacto significativo a nivel funcional y social, no así, en los resultados de calidad de vida y autoestima en este grupo.